The Analysis of Anxiety and Depression in Different Stages of in vitro Fertilization-Embryo Transfer in Couples in China - Liu YF; Fu Z; Chen SW; He XP; Fan LY (Neuropsychiatric Disease and Treatment, 2021)
Yao-Fang Liu,1 Zheng Fu,1 Shao-Wei Chen,1 Xiao-Ping He,2 Ling-Ye Fan1 1Department of Reproductive Technology, The Affiliated Hospital of Southwest Medical University, Luzhou, 646000, People’s Republic of China; 2Department of Prosthodontics, The Affiliated Stomatological Hospital of Southwest Medical University, Luzhou, 646000, People’s Republic of ChinaCorrespondence: Ling-Ye FanDepartment of Reproductive Technology, The Affiliated Hospital of Southwest Medical University, No. 25 of Taiping Street, Jiangyang District, Luzhou, 646000, People’s Republic of ChinaTel/Fax +86 0830 3165649Email lingyefan_cnsd@163.comBackground: This study aimed to examine the differences in anxiety and depression between infertile Chinese couples in diverse stages of in vitro fertilization-embryo transfer (IVF-ET) and their relationship with the IVF-ET outcomes.Methods: From February 2016 to December 2018, a total of 247 couples that were undergoing IVF-ET were randomly selected for this study. On the day they started their treatment (T1), the day human chorionic gonadotropin was administered (T2), and 4 days after the embryo transfer (T3), self-designed questionnaires, the Self-Rating Anxiety Scale, and the Self-Rating Depression Scale were completed to investigate anxiety and depression in different stages.Results: Age had an effect on the anxiety and depression in women. Male infertility type and the cause of infertility had an effect on the anxiety and depression in men. The incidence of anxiety in women in the T1, T2, and T3 stages was 29.96%, 44.94%, and 17.81%, respectively. The anxiety scores of women were 46.14 ± 8.37, 50.83 ± 8.50, and 44.09 ± 8.17, respectively, which were significantly higher than those of men (p < 0.05). The anxiety score in stage T2 was the highest in women, and the depression score of women in stage T1 was the highest. The incidence of anxiety in men in the T1, T2, and T3 stages was 20.65%, 8.50%, and 6.07%, respectively. The incidence of anxiety was not significantly different in diverse stages (p > 0.05), and the same result was obtained for the incidence of depression. The anxiety and depression scores of the infertile couples in different stages were not related to the outcome of IVF-ET.Conclusion: The incidence of anxiety and depression in infertile couples in diverse stages of IVF-ET is different, especially in women, and the anxiety and depression of infertile couples in the process of IVF-ET may not be related to the outcome of assisted pregnancy.Keywords: anxiety, couple, depression, in vitro fertilization-embryo transfer, outcome